2014
DOI: 10.1371/journal.pone.0094463
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Irisin Levels Are Not Affected by Coffee Intake: A Randomized Controlled Trial

Abstract: Irisin, secreted by skeletal muscle and possibly fat, is hypothesized to play an important role in modulating energy expenditure, obesity and metabolism. Coffee consumption also increases energy expenditure and leads to positive metabolic effects, but whether these effects are mediated by irisin remains unknown. The objective of this study was to determine the association between baseline irisin levels and the metabolic profile in humans and to investigate whether consumption of caffeinated coffee alters irisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
3
7
2
1
Order By: Relevance
“…This was important given the limited studies of irisin in the pediatric age group, and some uncertainty regarding expected values in a pediatric population. Of note, this assay reports irisin levels that are an order of magnitude higher than the Phoenix Pharmaceuticals assay [20]. All samples were processed immediately and stored at −80 degrees Celsius until they were analyzed to minimize peptide degradation, and contrary to one study that demonstrated inverse associations of irisin levels with duration of sample storage [21], we found no such inverse association of irisin or FGF-21 levels with duration of storage.…”
Section: Methodscontrasting
confidence: 80%
“…This was important given the limited studies of irisin in the pediatric age group, and some uncertainty regarding expected values in a pediatric population. Of note, this assay reports irisin levels that are an order of magnitude higher than the Phoenix Pharmaceuticals assay [20]. All samples were processed immediately and stored at −80 degrees Celsius until they were analyzed to minimize peptide degradation, and contrary to one study that demonstrated inverse associations of irisin levels with duration of sample storage [21], we found no such inverse association of irisin or FGF-21 levels with duration of storage.…”
Section: Methodscontrasting
confidence: 80%
“…54 In line with these findings, other studies showed a positive correlation between irisin and insulin resistance, which was assessed by the homeostasis model of assessment of insulin resistance (HOMAR-IR) index. 35,39,41,50,[55][56][57] All of these results were in line with Boström et al, who proposed a protective effect of irisin against insulin resistance. 2 When analysed the association between irisin and metabolic syndrome (MetS), a combination of various medical disorders including obesity and insulin resistance, higher circulating irisin levels in patients with MetS were also reported, when compared with patients without MetS.…”
Section: Irisin and Metabolic Diseasessupporting
confidence: 86%
“…2 Regarding obesity, a negative correlation was reported between irisin and BMI (body mass index) in several studies. 11,[30][31][32][33][34] These results were in line with the irisin's anti-obesity effect defended by Boström et al 2 However, controversy existed, as other studies founded no correlation, 17,35,36 or either a positive correlation. 25,[37][38][39][40][41][42][43][44][45] Roca-Rivada et al proposed that irisin was not only a myokine, but it was also an adipokine.…”
Section: Irisin and Metabolic Diseasessupporting
confidence: 70%
“…Of these, the vast majority of articles were excluded from the meta-analyses since they failed to report the association between circulating irisin and insulin resistance, or enrolled patients with diabetes. After further examination of the identified articles, 2 of them comprised 2 separate studies each [17,26], and 1 had raw datum obtained from the corresponding author [1], therefore, 19 studies in 17 articles were finally included in the meta-analyses [1,[11][12][13][14][15][16][17][26][27][28][29][30][31][32][33][34].…”
Section: Search Resultsmentioning
confidence: 99%